Dietary index for gut microbiota, metabolic syndrome, and long-term mortality: National Health and Nutrition Examination Survey, 2007–2018 - Yangyang Zheng; Tong Li; Hongyuan Cui; Jinghai Song (Diabetology & Metabolic Syndrome)
Abstract Background The pathogenesis of metabolic syndrome (MetS) is strongly linked to dysbiosis in the gut microbiota. However, studies investigating the association between the dietary index of gut microbiota (DI-GM) and MetS are limited. As such, the present study aimed to examine the association between DI-GM and the prevalence of MetS, as well as long-term mortality among individuals in the United States. Methods Data from 30,372 participants, obtained from the 2007 to 2018 cycle of the National Health and Nutrition Examination Survey, were analyzed. Associations between DI-GM scores and the prevalence of MetS and long-term mortality were examined using weighted logistic regression and Cox regression, respectively. Restricted cubic spline (RCS) and subgroup analyses were performed to further explore these relationships. Results An inverse association was observed between DI-GM and the prevalence of MetS, with each 1-unit increase in DI-GM corresponding to an 8.2% decrease in MetS prevalence (odds ratio 0.918 [95% CI 0.896–0.941]). Among participants with MetS, a 1-unit increase in DI-GM was associated with reduced risk for cardiovascular mortality (hazard ratio 0.922 [95% CI 0.854–0.994]). RCS analysis revealed a significant linear inverse association between DI-GM scores and MetS prevalence and cardiovascular mortality among participants with MetS. Subgroup analyses suggested that race, income level, and smoking status may modify the association between DI-GM and MetS prevalence. Conclusions Findings revealed that higher DI-GM scores were significantly associated with a lower prevalence of MetS in the general population and a reduced risk for cardiovascular mortality among individuals diagnosed with MetS. Further longitudinal studies are needed to confirm these associations and explore the underlying biological mechanisms.